Preliminary Experimental Investigation on the Filtration Performance of Submicron Insoluble Aerosol in a Bubble Column - Li, Yingzhi; Shi, Kaiyi; Sun, Zhongning; Gu, Haifeng; Zhou, Yanmin (Frontiers in Energy Research, 2019)
Pool scrubbing is a representative process for aerosol retention involved in the LWR severe accidents and has proved to be a potential method to removal micron-sized aerosol. Bubble scrubbing as the key component of pool scrubbing, has the advantages of large gas-liquid contact area and long residence time. However, the filtration mechanism of submicron aerosol by bubble scrubbing is still not clear. Therefore, the goal of this research is to evaluate the filtration performance of submicron insoluble aerosol in a bubble column. Some preliminary experiments were carried out to investigate the influence of operation parameter on aerosol filtration efficiency, such as inlet aerosol concentration, gas flow rate and pool temperature. Mass method was used to analyze the aerosol filtration efficiency. The results show that the aerosol filtration efficiency independent of inlet aerosol concentration when inlet aerosol concentration is in the range of 0.2-0.5 g/m3. Besides the aerosol filtration efficiency is influenced by the superfical gas velocity. With the increase of superfical gas velocity, homogeneous bubbling, transition and heterogeneous bubbling regime will appear in turn. The aerosol filtration efficiency decreases in transition regime due to the appearance of large bubble, but increases in heterogeneous bubbling regime account for intense gas-liquid interaction. Moreover, the aerosol filtration efficiency significantly decreases with pool temperature. Because the evaporation rate at the gas-liquid interface will significantly increase as the boiling point is approached, which gives retroaction to aerosol filtration efficiency.